Comparative Mechanical Performance of FDM-Printed PETG and ABS at Different Infill Percentages - Saeful Rofi Romadhon; Baharudin Priwintoko; Wahyu Hidayat; Baskara Surya Widagdo (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
The use of Fused Deposition Modeling (FDM) in additive manufacturing requires a material selection strategy that considers not only strength, but also the balance between stiffness, ductility, toughness, and surface resistance. This study evaluates the comparative mechanical performance of Acrylonitrile Butadiene Styrene (ABS) and Polyethylene Terephthalate Glycol (PETG) at 25%, 50%, 75%, and 100% infill using FDM printing and performance-map analysis. Specimens were designed according to ASTM standards and printed using the same printer, hexagonal infill pattern, print speed, and build orientation, while material-specific parameters such as extrusion temperature, heated bed temperature, layer height, first-layer height, enclosure, and cooling fan setting were adjusted according to ABS and PETG processing requirements. Mechanical characterization included tensile, flexural, impact, Shore D hardness, and density tests. The highest tensile strength was obtained by PETG at 100% infill, reaching 40.74 MPa, while ABS at the same infill reached 38.72 MPa. PETG also showed the highest elongation at break of 16.16%, flexural strength of 59.51 MPa, and impact strength of 0.053 J/mm². In contrast, ABS produced the highest surface hardness, reaching 84.17 Shore D at 100% infill, compared with 80.42 Shore D for PETG. The density values of both materials increased with infill and became similar at 100% infill, namely 1.00 g/cm³. These findings confirm a clear trade-off between strength, toughness, resilience, and hardness in FDM materials. PETG offers a more balanced mechanical profile for applications that require strength, deformation tolerance, and impact resistance, while ABS remains relevant for applications that prioritize rigidity and surface hardness.